Дослідження кінетики руйнування низьколегованих сталей після прискореного охолодження - Микитан, Ілля Андрійович (Харківський національний автомобільно-дорожній університет, 2025)
Object of research: fracture processes of low-carbon low-alloy steels in the bainite-martensitic structural state. Purpose of work: study of the relationship between post-deformation cooling regimes, the final structure and morphology of fracture surfaces of rolled metal from low-carbon low-alloy steels. Research methods: metallographic analysis; scanning electron microscopy; transmission electron microscopy; methods of testing mechanical characteristics; methods of mathematical processing of experimental data arrays. Results and their novelty. The morphological features of the structural state of low-carbon low-alloy steel after various heat treatment regimes were investigated. The influence of heat treatment regimes on the complex of mechanical properties of low-carbon low-alloy steel was investigated. The kinetics of fracture of low-carbon low-alloy steel samples depending on the structural state were investigated. Also the value of the crack propagation resistance coefficient was determined (quantitative fracture analysis); a mathematical model of the dependence of the crack propagation resistance coefficient on the parameters of the structural state was constructed.
Keywords: alloy steel; accelerated cooling; low-carbon low-alloy steel; heat treatment; spectral analysis; mechanical properties; fracture structure; quasi-brittle fracture